The Service-Bond Paradigm—Potentials for a Sustainable, ICT-enabled Future - Farrahi Moghaddam, Reza; Lemieux, Yves; Cheriet, Mohamed (EAI Endorsed Transactions on Smart Cities, 2016)
The service paradigm has gone through a long journey of evolution and improvement. A service-oriented vision to activities in general could serve as a platform for the global transition to a sustainable future. However, the services themselves are required to move beyond their traditional definition in order to prevent any secondary side effect. Here, a new paradigm is proposed based on bonding between entities involved in a service interaction, service chaining, or service orchestration. It is purposed to serve as a vehicle to approach sustainability at the global level in a manner that is thoughtful, collaborative, and incremental. The service bonds are then simply generalized toward representing bonding among more than two entities. Finally, a practical application of ICT agents in enabling the service bonds is presented in a use case related to smart houses along with some ICT-based agents (federal regulars, among other ICT agents).